Management Pengendalian Kualitas Batubara Berdasarkan Parameter Kualitas Batubara Mulai Dari Front Sampai Ke Stockpile Di PT. Budi Gema Gempita, Merapi Timur, Lahat, Sumatera Selatan. - Fitri Rahma Yenni; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. Pt. Budi Gema Gempita (PT. BGG) is one of the companies engaged in coal mining with the mining system implemented is the open pit mining system. coal produced by PT. BGG consists of different types grouped by their caloric value. To maintain the quality of coal, the company must have a coal quality control management team based on coal quality parameters, namely a series of activities in controlling the quality of coal, because in the process there is a decrease in the quality of coal that is when coal is mined (coal getting), then the accumulation of coal from the Front to the Stockpile area. Parameters used to maintain the quality of coal both clamped and stockpiled are total moisture (%),volatille matter, calories, ash content (%),), total sulphur (%). After sampling obtained results Coal quality on the mining front has a total moisture value (ARB) of 29.84%, inherent moisture value of (-)%, ash content value of 2.42%, volatile matter value of 32.56%, fixed carbon value of 35.18%, total sulfur value of 0.27% and calorie value of 4846 Kcal/kg, while the quality of coal distockpile ARB has a total moisture value of 30.01%, inherent moisture value of (-)%, ash content value of 2.65%, volatile matter value of 33.30%, fixed carbon value of 32.16%, total sulphur value of 0.30% and calorie value of 4866 Kcal/kg. The higher the fixed carbon value, the higher the caloric value.The lower the fixed carbon value, the ash content, moisture content and sulfur content will be higher.  Keywords: Coal, Pit channel, coal parameters, Stockpile, SOP Quality Control.